Is There a Global Safe Haven?1 . (December 2015) - Habib, Maurizio Michael; Stracca, Livio
Abstract: In this paper we search for global safe‐haven assets by analysing the impact of crisis episodes and risk shocks on the behaviour of foreign investors and selected asset prices and yields. We regress de‐trended net purchases by foreign investors of debt instruments issued in safe and liquid financial markets on estimated global risk‐aversion shocks and crisis episodes identified by both quantitative and qualitative means. On the price side, we also look at changes in long‐term government bond yields and the appreciation of the effective exchange rate conditional on risk shocks. We find that US short‐term debt – in particular government debt – is the best, though still imperfect, example of a global safe‐haven asset. In the majority of cases we find that foreign investors head for the exit.